Sintesis komposit karbon aktif TKKS/TiO2 terimmobilisasi pada polimer polipropilena sebagai agen remediasi POME - Muhammad Haykal Hafiz Aswan; Dwiria Wahyuni; Yudha Arman (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
The palm oil industry produces solid waste in the form of empty fruit bunches (EFB) and liquid waste known as Palm Oil Mill Effluent (POME). This study aims to synthesize an activated carbon composite based on EFB/TiO2 immobilized on polypropylene (PP) polymer and analyze its performance as a POME remediation agent. EFB carbon was activated using a microwave activation method to increase its surface area and adsorptive properties, then composited with TiO2 at 15% of the carbon mass. The resulting composite was then deposited on PP through a thermal milling process at two operating temperatures: 200°C and 220°C. This process causes the PP, which serves as the immobilization medium, to contain the composite on its surface, hereinafter referred to as carcom balls. Test results indicate that carcom balls are capable of reducing Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS) in POME. The BOD reduction efficiency of carcom balls at thermal milling temperatures of 200℃ and 220℃ was 36.8% and 41.4%, respectively, while the COD reduction efficiency was recorded at 41.1% and 45.1%. Meanwhile, the TSS reduction efficiency was 41.0% and 41.1%, respectively. Overall, carcom balls produced at 220℃ showed the highest remediation performance against POME.